Modern strategies in teaching: a theoretical study (Journal of Human Sciences, 2021)
The progress of science and technology represents an extraordinary challenge for pedagogical systems at educational institutions. There are massive information and knowledge that are twinned with scientific and technological progress. For the most part, that amount of knowledge is now available and waiting for students and teachers to deal with them. For this reason, it becomes an important matter to speak about this burst of knowledge. In fact, the advances in science accelerated rapidly; therefore, the burst of knowledge introduced several inquiries about learning and teaching. On one hand, regarding learners, the quantity of knowledge is not as important as its quality. What is also important is: how to reach, generate, invent, increase the mental capability, and how to deal with various resources of knowledge. On the other hand, to achieve optimum progress for the current curriculum, it should review the way of teaching. That could be done by elevating the classical teaching strategies or replacing them with modern teaching strategies. The aim of this article is to present an advanced understanding of teaching strategies. Therefore, the first item of this research introduces the subject, the second presents the meaning of strategies and scientific stations, the third revolves around the criteria, targets, and classifications of teaching strategies, the fourth includes old strategies whereas the fifth introduces modern strategies.